Prevalence, Risk Factors and Differential Diagnosis of Cystic Ovarian Degeneration in Crossbred Cows - Chauhan, JH; Hadiya, KK; Dhami, AJ (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present study was conducted under field conditions on >90 days postpartum HF crossbred cows with cystic ovaries (n = 58). Thediagnosis was confirmed by history and trans-rectal palpation and ultrasonographic examinations twice at weekly interval using 5.0–7.5MHz frequency probe and was later authenticated with plasma progesterone assay and treatment response. The animals with follicularcysts were randomly treated with either conventional ovsynch or ovsynch + CIDR protocol with fixed time AI (n = 10 each), and thosewith luteal cysts with either double PG injections 11 days apart or modified Ovsynch protocol (n = 16 each). Among 58 cystic cows,the highest incidence (62.07 %) of the ovarian cyst was recorded in the age group of 5–7 years followed by above 7 years (36.21%) and3–5 years (2.00%). The incidence was highest among cows of 3rd or more parity (70.69%) followed by 2nd parity (29.31%), and no casewas seen in primiparous cows. Of the total 36.21% were follicular type cyst and 63.79% luteal type cysts. The right ovary had a highincidence of the cyst (51.72%) followed by the left ovary (36.21%), and bilateral (12.07%). Based on rectal palpation, the cystic ovary wasclassified to have follicular cyst in 36.21% (21/58) cases and luteal cysts in 63.79% (37/58). Ultrasound examination showed follicularand luteal cysts as 27.59% and 72.41%, whereas plasma P4 ( 1 ng/mL) analysis revealed this as 20.69% and 79.31%, respectively.The clinical diagnosis became more accurate with a combination of per rectal palpation and USG and was further improved by plasmaprogesterone assay. The mean diameters and a wall thickness of cysts varied highly significantly (p
Keywords: Crossbred cattle; Differential diagnosis; Ovarian cysts; Prevalence; Risk factors; Treatment response; Ultrasonography